2005
DOI: 10.1073/pnas.0407698102
|View full text |Cite
|
Sign up to set email alerts
|

Lipofuscin accumulation, abnormal electrophysiology, and photoreceptor degeneration in mutant ELOVL4 transgenic mice: A model for macular degeneration

Abstract: Macular degeneration is a heterogeneous group of disorders characterized by photoreceptor degeneration and atrophy of the retinal pigment epithelium (RPE) in the central retina. An autosomal dominant form of Stargardt macular degeneration (STGD) is caused by mutations in ELOVL4, which is predicted to encode an enzyme involved in the elongation of long-chain fatty acids. We generated transgenic mice expressing a mutant form of human ELOVL4 that causes STGD. In these mice, we show that accumulation by the RPE of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
178
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(192 citation statements)
references
References 18 publications
11
178
1
2
Order By: Relevance
“…The current study as well as others (7,31,35) have shown that tagged-MUT is mislocalized in cultured cells. Mislocalization of the tagged-MUT to photoreceptor outer segments and inner retinal layers in transgenic pigs results in aberrations in photoreceptor structure and function (46).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The current study as well as others (7,31,35) have shown that tagged-MUT is mislocalized in cultured cells. Mislocalization of the tagged-MUT to photoreceptor outer segments and inner retinal layers in transgenic pigs results in aberrations in photoreceptor structure and function (46).…”
Section: Discussionsupporting
confidence: 81%
“…Several groups have shown interaction between wildtype and mutant protein (8,31,35), suggestive of a possible dominant-negative effect in disease manifestation. To determine the influence of this interaction on the enzymatic activity of ELOVL4, we coexpressed untagged ELOVL4 with each of the HA-tagged constructs (WT, MUT, and mERET) in ARPE19 cells.…”
Section: Stgd3 Mutant Has a Dominant-negative Effect On Elovl4 Localimentioning
confidence: 99%
“…53 The connection of the complement system to AMD has been reported in some murine models of dry-type AMD. 25,44,51,52,54,57,62 Retinal abnormalities have been described in aged FH deficient (Cfh À/À ) mice. 51 However, the disease phenotype was modest because these animals displayed a partial phenotype of dry AMD.…”
Section: Discussionmentioning
confidence: 99%
“…T hree independent mutations in the last exon (exon-VI) of the ELOVL4 gene are associated with dominant Stargardt-like macular dystrophy (STGD3) in humans (1)(2)(3)(4). These mutations cause a frame-shift that introduces a stop codon, resulting in premature termination of the protein and removal of the signal sequence for targeting the protein to its putative cellular location, the endoplasmic reticulum (1,4).…”
mentioning
confidence: 99%
“…These mutations cause a frame-shift that introduces a stop codon, resulting in premature termination of the protein and removal of the signal sequence for targeting the protein to its putative cellular location, the endoplasmic reticulum (1,4). As a result, the mutant protein mis-localizes and aggregates (3,5,6), and, when coexpressed with the wild type protein, the mutant and wild-type proteins associate and mis-localize (3,7).…”
mentioning
confidence: 99%